2011
DOI: 10.1111/j.1467-9876.2011.01005.x
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Method for Confirmatory Evaluation of the Effects of a Covariate in Multiple Models

Abstract: Summary.  Modern epidemiology often requires testing of the effect of a covariate on multiple end points from the same study. However, popular state of the art methods for multiple testing require the tests to be evaluated within the framework of a single model unifying all end points. This severely limits their use in applications where there are different types of end point, e.g. binary, continuous or time to event. We use an asymptotic representation of parameter estimates to combine multiple models without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
106
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(106 citation statements)
references
References 23 publications
0
106
0
Order By: Relevance
“…The proposed method is less conservative than the Bonferroni-type correction if the test statistics are substantially correlated. This results in smaller adjusted p values, as demonstrated in the Applications section (see also the Discussion section in Pipper et al [17] ).…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…The proposed method is less conservative than the Bonferroni-type correction if the test statistics are substantially correlated. This results in smaller adjusted p values, as demonstrated in the Applications section (see also the Discussion section in Pipper et al [17] ).…”
Section: Discussionmentioning
confidence: 75%
“…To make a conclusion about the underlying mode of inheritance, we need to consider simultaneous inference on the parameter vectors from the three genetic models β (123) = ( β (1) , β (2) , β (3) ). We use the multiple marginal models approach of Pipper et al [17] who introduced a flexible procedure for evaluation of effects in parallel models for multiple endpoints; a related approach was proposed by So and Sham [18] . Specifically, Pipper et al [17] showed that the asymptotic results for the three single GLMs also hold when stacking the corresponding three ML estimators into a single vector:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations